Influence of the plasma environment on auto-ionization. (15th August 2016) - Belkhiri, Madeny; Fontes, Christopher J
Abstract: In this work, we show the influence of the plasma environment on the auto-ionization rate using an ion-sphere model. We consider transitions from the He-like to the H-like ion stage of aluminum for illustrative purposes, but the approach is completely general and can be applied to arbitrary, highly charged ions. A detailed numerical investigation and comparison is made between two independent computational schemes, using the relativistic configuration-average, distorted-wave approach. We show that the decreasing behavior of the auto-ionization rates as a function of free-electron density is due to a change in the quantum interference between the bound and free electrons, and also provide a qualitative explanation of this trend.